THE LETTERS OF LADY ANNE BACON. (20th March 2014) - Unknown
Abstract : Published, prefatory letter. B. Ochino, Sermons of Barnadine Ochine of Sena godlye, frutefull, and very necessarye for all true Christians, trans. anon (London, 1548), sigs A2r–A4r.